Philosophical Hierarchy and Deconstruction of Structure in Bukit Mawar Short Story - Ide Idola Silehu; Sabrina Wardatul Jannah Husain (Alphabet: A Biannual Academic Journal on Language, Literary, and Cultural Studies, 2021)
In Derrida’s deconstruction regarding the reading of philosophical hierarchy,two things are positioned as “superior” cases and special cases that are “lost/marginalized”. Deconstruction occurs when a story changes in terms of its form, where the “superior”consistently dominates the “inferior”. Derrida shows how the term “superior” depends on the term “being suppressed” (marginalized) in the process of accumulating its own meaning. He detects true social norms and standards that derive its identity and authority in exclusion measures through differentiation. The steps involved in Derrida’s deconstruction analysis of a literary work are, first,to break down the existing hierarchy. The second is the stage of deconstructing and changing the meaning. To deconstruct and replace the hierarchy, Derrida shows how the “superior” depends on the “being suppressed” (marginalized). In Yanusa Nugroho’s Bukit Mawar short story, the deconstruction of philosophical hierarchy can be found in several character traits and dialogue quotes. The social status and views of society that are presented in the work are also a deconstruction of the structure of social life as it should be.Keywords: philosophical hierarchy, deconstruction of structure, Bukit Mawar